A CURICULUM DRIVEN FRAMEWORK FOR ENHANCING THE QUALITY OF ISLAMIC HIGHER EDUCATION : A THEORETICAL SYNTHESIS - Permadi, Adi; Muhammad Aufakumara Sucipto; Djamaluddinn Perawironegoro (As-Sulthan Journal of Education, 2026)
Improving the quality of Islamic education in higher education institutions is a strategic necessity to produce graduates who excel in knowledge, character, and morals. However, research indicates that quality remains relatively low due to curricula that are unresponsive to modern developments, lecturer-centered teaching methods, and limited learning facilities. This study aims to analyze the relationship between the Islamic education curriculum and quality improvement strategies through a qualitative library research approach, analyzing scientific journals, academic books, and educational regulations. The results show that strengthening educational quality can only be achieved if the curriculum serves as an integrative axis coordinating teaching quality and facility provision. The resulting integration model consists of three pillars: competency-based curriculum revision, enhanced lecturer competence through interactive pedagogical innovation, and investment in technology-based learning facilities. These pillars form a holistic learning ecosystem to produce graduates who are scientifically competitive, technologically adaptive, and spiritually grounded. These findings confirm that curriculum reform must be accompanied by a transformation of pedagogy and infrastructure to meet contemporary needs without losing Islamic values.